Effect of capital structure and financial performance upon company value of automotive and components industrial subsectors which are registered in BEI - Syarief Gerald Prasetya; Raisa Nazila (STIE Binaniaga, 2019)
Automotive industry is an industrial subsector that is attractive to be studied in a developing country and is one of the most important economic sectors in the world due to the revenue and strategic issue as it is not only providing a lot of benefits for national prestige, technology development, but also manpower employment. The purposes of this research are as the following: 1. To find out the effect of capital structure upon value of the company. 2. To find out the effect of financial performance upon value of the company. 3. To find out the effect of capital structure and financial performance upon value of the company. Population of this research is financial statement of manufacturing companies which is automotive and components industrial subsectors which are registered in the Indonesian Stocks Exchange (BEI) period 2009 – 2014. The samples are financial statement of the manufacturing companies registered in BEI. Data analysis instrument has applied multiple linear regression using SPSS software. Outcome of the research; 1. Capital structure variable partially has positively affected company value, therefore, in order to increase value of the company, variable of capital structure should have to be increased accordingly. 2. Financial performance variable partially has positively affected company value, therefore, in order to increase value of the company, variable of financial performance should have to be increased absolutely 3. Capital structure and financial performance variables simultaneously have positively affected company value. Independent variable which has mostly affected the company value is financial performance variable, it has been indicated by the value of β Standardize Coefficience of 32.715 Keywords: Capital Structure, Financial Performance and Value of the company.